QUR'AN'S ETHOS OF JUSTICE ON WEALTH DISTRIBUTION THE TIME OF THE PROPHET AND COMPANIONS - Desri Ari Enghariano; Ihdi Aini; Sawaluddin Siregar (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2026)
Inequality in the distribution of wealth has been a structural problem since pre-Islamic times to the modern era, including in Indonesia, where wealth tends to be concentrated in elite groups. This study aims to examine historically and normatively the ethos of justice in the distribution of wealth during the time of the Prophet Muhammad PBUH and his companions as a conceptual model to formulate the principle of sustainable economic justice. The research uses a qualitative-descriptive approach with normative-historical analysis to trace the values, policies, and practices of justice applied in early Islamic societies. The results of the study show that the Prophet PBUH built the foundation for wealth distribution through zakat, the prohibition of usury and hoarding, as well as ethical market arrangement. While the Khulafaur Rasyidin developed the system through the supervision of official assets, strengthening the baitul mall, fiscal reform, and the principle of equitable distribution of public assets. The findings show that economic justice in Islam is structural and preventive, aiming to protect the weak and prevent the concentration of wealth. The implications of the study confirm that the value of the distribution of wealth during the time of the Prophet and his companions is relevant as an ethical framework and public policy in dealing with modern economic inequality.